Bispecific radioligands targeting prostate‐specific membrane antigen and gastrin‐releasing peptide receptors on the surface of prostate cancer cells. (11th July 2019) - Liolios, Christos; Sachpekidis, Christos; Schäfer, Martin; Kopka, Klaus
Abstract : Metastases of prostate cancer usually show highly heterogeneous or partly lost prostate‐specific membrane antigen (PSMA) expression. In order to image and treat both PSMA positive and negative tissues, the extension of PSMA tracer specificity to other receptors, also highly expressed on the surface of prostate cancer cells, has been suggested. Prostate cancer cells usually express both PSMA and gastrin‐releasing peptide (GRP) receptors; thus, bispecific heterodimeric molecules, addressing both targets at the same time, may significantly improve prostate cancer imaging and therapy. This article summarizes preclinical data regarding low‐molecular weight molecules targeting PSMA and GRP receptors. Abstract : This article summarises preclinical data of bispecific heterodimeric molecules targeting prostate‐specific membrane antigen (PSMA) and gastrin‐releasing peptide (GRP) receptors on prostate cancer tumor cells.